COCRYSTALS: A COMPLETE REVIEW ON CONVENTIONAL AND NOVEL METHODS OF ITS FORMATION AND ITS EVALUATION - BIJAY KUMAR YADAV; ATIF KHURSHEED; RATTAN DEEP SINGH (Asian Journal of Pharmaceutical and Clinical Research, 2019)
The active moiety with poor solubility is posing a challenge in drug development which may reduce the effectiveness in patients when administered orally. Cocrystal formation is one of the latest approaches for improving the various parameters of a drug molecule such as solubility, melting point, pharmacokinetic, pharmacodynamic, and bioavailability. Cocrystals are crystalline single state materials composed of two or more than two different molecular amalgams held together in a fixed stoichiometric ratio. There are various techniques used for the preparation of cocrystals such as solvent evaporation, grinding, and cooling crystallization. The quantitative and qualitative aspects of these cocrystals are evaluated using various validated instruments such as nuclear magnetic resonance, powder X-ray diffraction, and differential scanning calorimetry.